The theory behind vessel length determination using gas flow rates and comparison between two pneumatic methods based on seven woody species. (11th May 2022) - Peng, Guoquan; Geng, Hongru; Li, Yaxin; Ren, Zhiyang; Peng, Juan; Cao, Lei; Pereira, Luciano; Tyree, Melvin T; Yang, Dongmei
Abstract : Improved pneumatic theories show that data for gas flow rates versus stem segment lengths obtained from inexpensive 'Pneumatron' devices can produce accurate results for vessel length distribution in woody species. Abstract: In plants, xylem vessel length is important for long-distance water transport; however, the currently used methods for vessel length measurement are inconvenient and time-consuming. The recently developed semi-automated Pneumatron is a device based on the pneumatic theory that is similar to the air-injection method, and can rapidly estimate vessel length. Mean vessel length was compared between the Pneumatron and the air-injection method in seven woody species with a wide range of vessel lengths (2.3–78.7 cm). The results were consistent between the two methods, regardless of whether the same or different samples were used. The theory underlying the gas flow in vessels was improved and expanded, and compared to that underlying the water flow in order to better understand the pneumatic processes within a stem sample. Moreover, a new and simple equation for gas flow in vessels was derived based on the molar gas flow (mol s -1 ) rather than volume flow, because the former remains constant with distance throughout the stem axis. We strongly recommend using the Pneumatron in future studies owing to its low cost, convenience, rapidity, and simple operation. However, a number of potential issues need to be considered to avoid artifacts during measurements.